ADAPTATION OF INVESTMENT MANAGEMENT IN REAL PRODUCTION SECTOR OF THE RUSSIAN FEDERATION TO CONDITIONS OF SANCTIONS - Irina Solovyova; Oksana Takhumova (Вестник Северо-Кавказского федерального университета)
In this work the sources of information and methods allowing to determine an investment potential of the country at the regional level that allows to give the quality characteristic to each subject of the country and effectively to distribute investment flows are analytically considered. Conclusion of this article is that fact that in the conditions of the imposed sanctions and response embargo on a number of certain types of products, approach to investment management shall be based not only on data of the largest international rating agencies, but also on internal researches which results will allow to invest in real production sector of the Russian Federation most effectively.